Verbs' implicit causality in coreference and coherence processing during L2 comprehension - Masaya Hosoda (Frontiers in Language Sciences)
The existing psycholinguistic research suggests that verbs' implicit causality (IC) elicits two types of bias: a coreference bias, which favors re-mentioning the causally implicated entity of the event (she = Mary in Mary annoyed Lisa because she. ..), and a coherence bias, which leads speakers to expect an explanation in the upcoming discourse (Mary annoyed Lisa is continued with Mary sang loudly). Of these two biases, previous second-language (L2) studies have predominantly focused on coreference bias in contexts where an upcoming explanation is explicitly signaled (Mary annoyed Lisabecause...). The present study advances the L2 literature by examining both coherence and coreference biases in L2 comprehension. Eye-tracking and story-continuation experiments revealed that L2 learners are fundamentally weaker than native speakers in terms of coherence bias. As a result, an upcoming explanation must be explicitly signaled for IC to trigger coreference bias during online L2 processing. The findings suggest that while the underlying mechanism of IC bias functions similarly in both L1 and L2 comprehension, there is a pronounced L1–L2 difference in the ease with which an implicit explanation relation can be activated through expectation-based processing. The findings are discussed in terms of the source and time course of IC, as well as theoretical accounts of L2 prediction.